2000
DOI: 10.2337/diacare.23.9.1295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of peripheral vascular disease in a selected South Indian population: the Chennai Urban Population Study.

Abstract: OBJECTIVE -The epidemiology of peripheral vascular disease has rarely been studied in non-European populations. The purpose of this study was to determine the prevalence and risk factors of peripheral vascular disease (PVD) among South Indians. RESEARCH DESIGN AND METHODS -The Chennai Urban PopulationStudy is an epidemiological study involving 2 residential areas in Chennai in South India. Of the 1,399 eligible subjects (Ն20 years of age), 1,262 (90.2%) participated in the study. All of the study subjects unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
114
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(135 citation statements)
references
References 26 publications
(28 reference statements)
17
114
4
Order By: Relevance
“…The prevalence of CHD, measured as major Q wave changes was 3.9%, almost similar to Asian Indians in UK (4.0%) [24]. The prevalence of peripheral vascular disease (PVD) among Indians is 4-6% which is comparatively lower as compared to 9.3% among the white population [32]. Diabetic foot is a common cause of hospital admissions among diabetics in India.…”
Section: Complications Of Diabetesmentioning
confidence: 76%
“…The prevalence of CHD, measured as major Q wave changes was 3.9%, almost similar to Asian Indians in UK (4.0%) [24]. The prevalence of peripheral vascular disease (PVD) among Indians is 4-6% which is comparatively lower as compared to 9.3% among the white population [32]. Diabetic foot is a common cause of hospital admissions among diabetics in India.…”
Section: Complications Of Diabetesmentioning
confidence: 76%
“…5 Population data on micro and macro vascular complications of diabetes are available in urban India. [6][7][8][9][10] However, such data were not available in rural India. This is largely because in rural areas, diabetes remains a neglected field, as awareness levels and accessibility to diabetes health care remains woefully inadequate.…”
Section: Symposiummentioning
confidence: 99%
“…It has been observed in many studies that over 50% of patients with DM in India have a poor glycemic control and a substantial proportion amongst these also have diabetes-related complications [1]. According to the Chennai Urban Population Study (CUPS), the prevalence of coronary artery disease (CAD) was 21.4% (CUPS No 5) [2] and peripheral vascular disease (PVD) was 6.3% among patients of DM in South India [3]. Another study from North Delhi Diabetes centre comprising 720 T2DM patients, retinopathy was found in 21.2%, microalbuminuria in 41%, peripheral neuropathy in 15.3%, CAD in 7% and PVD in 7.4% of patients [1].…”
Section: Introductionmentioning
confidence: 99%